Coupled Monte Carlo and thermal-fluid modeling of high temperature gas reactors using Cardinal. (November 2022) - Novak, A.J.; Andrs, D.; Shriwise, P.; Fang, J.; Yuan, H.; Shaver, D.; Merzari, E.; Romano, P.K.; Martineau, R.C.
Abstract: Cardinal is an open-source application that couples OpenMC Monte Carlo transport and NekRS computational fluid dynamics to the Multiphysics Object-Oriented Simulation Environment (MOOSE), closing neutronics and thermal-fluid gaps in conducting high-resolution multiscale and multiphysics analyses of nuclear systems. We provide an introduction to Cardinal's software design, data mapping, and multiphysics coupling strategy to highlight our approach to overcoming common challenges in multiphysics simulation. We then describe an application of Cardinal to prismatic High Temperature Gas Reactors (HTGRs) with various combinations of NekRS, OpenMC, BISON, and THM. A high-resolution coupling of NekRS, OpenMC, and BISON provides a reference solution at the unit cell level and shows excellent agreement with a lower-resolution coupling of THM, OpenMC, and BISON. A full core coupling of THM, OpenMC, and BISON resolving the three-dimensional conjugate heat transfer and sub-pin power distribution then provides detailed predictions of HTGR temperatures and the fission distribution.